2020
DOI: 10.1039/d0cc05336h
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate-driven structural growth in Calix[n]arene-polyoxotitanate hybrid systems: utility in hydrogen production from water

Abstract: A carboxylate-driven assembly strategy has first been developed to build calix[n]arene-based polyoxotitanate clusters with tuneable nuclearity and structures. Photocatalytic studies revealed that those clusters exhibit structural-dependent H2 evolution ability with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Their unique properties, such as multiple active sites, diverse configurations, and rich coordination modes, make them one of the most attractive choices for use as modified ligands in TOCs. The use of calixarenes in metal coordination compounds has been intensively investigated; however, Ti-calixarene complexes have received far less attention than those of other metals. To the best of our knowledge, the first calixarene-protected TOC was published independently by Power and Atwood . Research work on the molecular structure, binding modes, and chemical modifications of these complexes has subsequently been published. Yuan et al isolated a monomeric bowl-like pyrogallol[4]­arene Ti 12 coordination complex, which is the highest-nuclearity TOC derived from calixarenes .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their unique properties, such as multiple active sites, diverse configurations, and rich coordination modes, make them one of the most attractive choices for use as modified ligands in TOCs. The use of calixarenes in metal coordination compounds has been intensively investigated; however, Ti-calixarene complexes have received far less attention than those of other metals. To the best of our knowledge, the first calixarene-protected TOC was published independently by Power and Atwood . Research work on the molecular structure, binding modes, and chemical modifications of these complexes has subsequently been published. Yuan et al isolated a monomeric bowl-like pyrogallol[4]­arene Ti 12 coordination complex, which is the highest-nuclearity TOC derived from calixarenes .…”
Section: Introductionmentioning
confidence: 99%
“…The use of calixarenes in metal coordination compounds has been intensively investigated; however, Ti-calixarene complexes have received far less attention than those of other metals. To the best of our knowledge, the first calixarene-protected TOC was published independently by Power and Atwood . Research work on the molecular structure, binding modes, and chemical modifications of these complexes has subsequently been published. Yuan et al isolated a monomeric bowl-like pyrogallol[4]­arene Ti 12 coordination complex, which is the highest-nuclearity TOC derived from calixarenes . More recently, Liu et al reported a family of calixarene-protected TOCs synthesized by a carboxylate-driven assembly strategy and investigated the structural dependence of the hydrogen-evolution ability of these TOCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each molecule comprises a Ti 4 O 4 ladder, with end chlorides 'up', and middle two chlorides 'down'. We note that calix[8]arene titanium ladder complexes have recently been isolated and utilized for CO 2 photoreduction and photocatalytic H 2 production 71–73 . In 10·6.5(MeCN), there are two triply‐bridging oxo bridges, and terminal coordinated MeCNs on the two end Ti ions.…”
Section: Resultsmentioning
confidence: 99%
“…For 10Á6.5(MeCN), two Ti 4 complexes and 13 MeCNs of crystallization are found in the We note that calix [8]arene titanium ladder complexes have recently been isolated and utilized for CO 2 photoreduction and photocatalytic H 2 production. [71][72][73] In 10Á6.…”
Section: Titaniummentioning
confidence: 99%